Nonlinear analysis of performance-determinant factors in competitive swimming - Bartolomeu, Raul Filipe Barbosa (2022)
The present work aimed to study the nonlinear behavior of performance-determinant variables, namely kinetic, kinematic and motor control in the four competitive swimming strokes, each subdivided into 3 variants: full-body stroke, arm-pull only and leg kicking only. Thus, the investigation comprises three cross-sectional experimental studies to assess velocity, propulsive force and limb asymmetry. The sample includes athletes with at least a two-year experience in regional/national championships. The testing took place in short-course pools (25m), where swimmers performed maximal bouts of 25m, interspersed with 30-minute rest intervals to ensure the athlete's recovery. For the evaluation of velocity, a mechanical velocity meter (Swim speedometer, Swimsportec, Hildesheim, Germany) was used and for the measurement of the propulsive force, a differential pressure measurement system (Aquanex, Swimming Technology Research, Inc.) was used. All data was, after collection, exported to a signal processor (AcqKnowledge v.3.7.3, Biopac Systems, Santa Barbara, USA) where was submitted to a low-pass, 4th order Butterworth filter for smoothing the sign. To assess the nonlinear behavior of the variables, the Higuchi’s fractal dimension (HFD) and the sample entropy (SampEn) were calculated in a MatLab routine (v.R20013a, MathWorks, Natick, USA). It was found that both velocity and propulsive force have non-linear properties, i.e., their behavior can be characterized through nonlinear analysis. Furthermore, the nonlinear properties are influenced not only by the swimming stroke, but also by the limbs in action. It was also verified that both the sum of the segmental velocity and the sum of the segmental propulsion force is greater than the velocity/propulsion force of the full-body stroke. This result was verified for all swimming strokes. The investigation in the first study showed that velocity tends to be less complex (lower HFD) and more predictable (lower SampEn) in the leg kicking condition than in the arm-pull and full-stroke conditions. The arm stroke on the other way tends to be more complex but more predictable than full-stroke swimming. Furthermore, strokes featuring simultaneous limbs’ actions are more complex and more predictable than the ones who feature alternate limbs’ actions. In the second study it was found that the propulsive force is more complex in breaststroke and butterfly in arm-pull conditions; on the other hand, the leg kicking tends to be more complex on front crawl and backstroke. Furthermore, the arm-pull and leg kick performed alone tend to be more complex but more predictable than when performed in the full-body stroke. xvi In the third study it was noted that all swimming strokes and their conditions presented asymmetries in the propulsive force production in both the upper and lower limbs. The asymmetry of the limbs negatively and slightly influences the complexity of propulsive force production. It was concluded that the variation of velocity, propulsive force and asymmetries among conditions can be deemed as constraints to swimming and can be further explored by coaches in the learning or training process.